Uma avaliação de usabilidade da aplicação web RST-IoT - Conceição, Bárbara Milena de Oliveira (Brasil, 2021)
With the advancement of the internet and the increase in the number of users interconnected by the world wide web, there was a need to improve the performance of the applications available on it, with a view to improving human-computer interaction. Thus, more and more companies, developers or even people, who offer some good or service in web applications, can use the focus on this interaction between user-application as a competitive advantage. In this perspective, the present study aimed to carry out a Usability Assessment in the RTS-IoT web application using the Heuristic Assessment technique. Through the results obtained, it was possible to suggest improvements to improve the quality of this system in relation to usability attributes.